Still no evidence that pathogen accumulation can revert the impact of invasive plant species - Chiuffo, Mariana Cecilia (2018)
As do Flory et al. (2017), we recognize the potential consequences of pathogen accumulation for the dynamics of invaded plant communities. We also agree that pathogen accumulation is an important area of research requiring more attention. However, we are still puzzled by the paucity of data showing that pathogen accumulation can control invasive species populations. Flory et al. (2017) mentioned several examples, but they are mostly for native species, non-invasive species, agricultural settings, or artificial inoculation with pathogens (e.g., Harris et al. 2013).